Identification of human genes potentially involved in the pathogenesis of viral hepatitis C based on multi-network bioinformatics analysis - Ekaterina V. Anufrieva; Yulia V. Ostankova; Vladimir S. Davydenko; Alexandr N. Schemelev; Areg A. Totolian (Вопросы вирусологии)
Aim. The aim of this study was to search for human genes potentially involved in the pathogenesis of hepatitis C by multi-network bioinformatics linkage analysis of proteins involved in the stages of hepatitis C virus (HСV) attachment and entry.